Fly guy presents : snakes - Arnold, Tedd. (New York, Scholastic Inc., 2016)
It's time for a field trip! Fly Guy and Buzz are going to the zoo to learn all about snakes. With straightforward text, humorous asides, and kid-friendly full-bleed photographs throughout, young readers will love learning about these slithery creatures.
1.9
K-3
610L
P
Keywords: Snakes -- Juvenile literature; Reptiles -- Juvenile literature; Snakes; Reptiles; Snakes; Reptiles; Snakes; Readers (Elementary) -- Nonfiction